2020
DOI: 10.1186/s13244-020-00845-y
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of bone following denosumab treatment: assessment of tumor response using various imaging modalities

Abstract: Background: Giant cell tumor (GCT) is a nonmalignant neoplasm composed of multinucleated giant and mononuclear stromal cells. This study aimed to compare imaging findings of GCT pre-and post-denosumab treatment, including lesion size, percentage of signal intensity/density change, and time of initial objective tumor response. This will have a great impact on selection of most appropriate imaging technique to accurately measure therapy response and its related complications, which would influence the physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…This finding could be further supported by the reduction of SUVmax in PET/CT after denosumab treatment (Figure 1D), which was also attributed to the elimination of the giant cells 8,25,30,31 . X-ray and CT examinations were used to evaluate the development of new ossification as well as increased cortical thickness 4,12,14,15,19,29,32,33 . In this study, we observed new ossification and reappearance of cortical integrity around the soft-tissue mass in both ultra-short group (15.6% and 12.5%) and conventional group (65.2% and 56.5%), with higher frequency in the latter group (Figure 3A–C).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This finding could be further supported by the reduction of SUVmax in PET/CT after denosumab treatment (Figure 1D), which was also attributed to the elimination of the giant cells 8,25,30,31 . X-ray and CT examinations were used to evaluate the development of new ossification as well as increased cortical thickness 4,12,14,15,19,29,32,33 . In this study, we observed new ossification and reappearance of cortical integrity around the soft-tissue mass in both ultra-short group (15.6% and 12.5%) and conventional group (65.2% and 56.5%), with higher frequency in the latter group (Figure 3A–C).…”
Section: Discussionsupporting
confidence: 62%
“…8,25,30,31 X-ray and CT examinations were used to evaluate the development of new ossification as well as increased cortical thickness. 4,12,14,15,19,29,32,33 In this study, we observed new ossification and reappearance of cortical integrity around the soft-tissue mass in both ultra-short group (15.6% and 12.5%) and conventional group (65.2% and 56.5%), with higher frequency in the latter group (Figure 3A-C). This result was in accord with the histological finding that more cases (92%) in the conventional group showed new bone formation than those in the ultra-short group (68.3%).…”
Section: Radiological and Histological Response Induced By Ultra-shor...supporting
confidence: 51%
“…Similar to osteoclasts, giant cells also express the RANK receptor on their surface, suggesting their formation as a result of fusion of monocytic precursors recruited by the stromal cells through the expression of RANKL, exactly as is the case for osteoclasts (Morgan et al, 2005). The high expression of RANKL within the tumor paved the way for the use of denosumab, a fully human monoclonal antibody to RANKL, as efficient treatment for GCT, reducing its lytic activity (Chawla et al, 2019;Alothman et al, 2020). Therefore, targeting giant cells is a more effective approach than targeting neoplastic stromal cells.…”
Section: Role Of Osteoclasts In Tumor Biology Primary Bone Tumorsmentioning
confidence: 99%
“…CT, magnetic resonance imaging (MRI), and positron emission tomography (PET) are useful for evaluating tumor response [ 52 , 53 ] and blood supply. Based on the inverse Choi density/size (ICDS) criteria assessed using CT or MRI images before and after treatment with denosumab, the majority of patients with GCTB have a significant tumor response [ 54 ]. Furthermore, PET helps assess early tumor response [ 55 ].…”
Section: Dose and Duration Of Therapy With Denosumab Affect The Blood...mentioning
confidence: 99%